(untitled) (Journal of Forensic Medicine & Toxicology, 2019)
The accidental or intentional intake of toxic plants can produce serious deleterious effects in the humans and livestock. There are several plants tagged with medicinal properties but are equally toxic when used ignorantly. However the magnitude of incidences of plant poisoning is not too high, but such cases cannot be ignore in a country like India, which has such diverse flora and where herbal formulations and homemade remedies are extensively used. Here in India, forensic science laboratories sometimes encounter such cases where suspected toxic plant needs identification for civil as well as criminal cases. The present study attempted to identify such potentially toxic plants and their toxicity cases happened during 2011-15 in livestock and humans.